Comparison of Command-Based vs. Reality-Based Interaction in a Veterinary Medicine Training Application - Franzluebbers, Anton; Platt, Simon; Johnsen, Kyle (Frontiers in Virtual Reality, 2020)
This paper presents a study evaluating alternative interaction styles for a novel virtual reality simulator proposed for veterinary neurology training. We compared a reality-based interaction metaphor, which is commonly used in virtual reality applications, to a command-based metaphor that reduced interactivity towards improving overall application usability. A cohort of 55 veterinary medicine students took part in the study, which took place at the veterinary school building. The study used a crossover design that allowed each participant to try both systems. Results suggested some correctable usability issues with the reality-based system, particularly the inclusion of haptic feedback for certain parts of the examination. A strong overall preference for the reality-based system was also observed. The study highlighted the potential of using both systems in tandem, with the command-based system being used prior to the reality-based system.